Effectiveness of Pyridoxin in Reducing Symptoms of Anxiety Pre Menstrual Syndrome in Adolescent - Siti Nurunniyah; Eva Nurinda (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Pre Menstrual Syndrome (PMS) affects women’s quality of life, social and economic performance. The other study discovered that 23- 31 % of reproductive aged women experience PMS to a degree that affects their daily acivity Symptoms of Pre Menstrual Syndrome (PMS) are divided into 4 types, namely type A for Anxiety (Anxiety), type C for Craving (Hungry), type D for Depression and Type H for Hyperhydration (Liquid Stockpiling). Type A is commonly unrecognnized in indonesia. Symptoms of type A consist of anxiety, irritability, labilty and nerves tense. So it is important to know how to reduce the symptoms This study aims to determine the effectiveness of pyridoxin in reducing symptoms of Pre Menstrual Syndrome (PMS) and type of symptoms that can be most resolved. There is an effect of using pyridoxine to reduce PMS. It is known from the significance value of t-test that is 0.000. The type of PMS with the highest symptom reduction is in PMS Type A (Anxiety), because pyridoxine can increase stability estrogen and progesterone activity. Anxiety Pre Menstrual Syndrome probably caused by unstable hormone.